Self-Actualization of Tallie Jones in Danielle Steel’s Betrayal - Eka Kurniawati; Anwari, Anwari; Hikmah, Uliyah; Isnina, Fathimah (Vilvatikta: Jurnal Pengembangan Bahasa dan Sastra Daerah, 2024)
The aim of conducting this study is to analyze self-actualization in Danielle Steel’s Betrayal. The main character Tallie Jones fulfills her need for self-actualization. She lives in a complicated world of untrustworthy people, dishonesty, and superficial values. She is betrayed by two people she loves and trusts and wants to figure out who is stealing money from her. The source of the data was a novel entitled Betrayal written by Danielle Steel. It was published in July 2012. This study used the theory of Abraham Maslow’s Hierarchy of Needs. It was arranged as follows: 1) the physiological needs, 2) the safety needs, 3) the belongingness and love needs, 4) the esteem needs, and 5) self-actualization needs. Self-actualization was the culmination of the fulfillment of human needs. In analyzing this study the writer used library research. The researchers also used a concept analysis. They related and explained the object to theories, concepts, or other relevant sources. Based on analysis, the writers obtained some significant evidences concerning self-actualization needs. Tallie Jones manages to struggle through several stages to deal with her complicated problem. She grieves and weeps. But, finally, she finds a lover and can actualize herself as an incredible woman in the world.